A biomechanical analytical study of child athletes aged 8 to 16 years - Jabara, Asst.L.Sajjad Hassan Maktoof; Ati, Asst.L.Jassim Jabara Jassim (Sulaimani Journal for Humanities, 2026)
This research presents a biomechanical analysis of child athletes aged 8 to 16 years. Accident dynamics, passenger characteristics, and injury patterns were analyzed, leading to the identification of factors contributing to injury severity. The findings are consistent with current literature on motor vehicle accidents but also highlight the unique challenges of road safety in Iraq. The study underscores the need for a comprehensive approach to injury prevention and mitigation, including improving road infrastructure, enforcing traffic safety regulations, and raising public awareness. It also emphasizes the importance of enhancing vehicle safety features and improving emergency medical response. The study recommends further research to collect comprehensive data on accidents and injuries in Iraq, develop culturally appropriate road safety education interventions, and foster collaboration among researchers, vehicle manufacturers, and policymakers.
Keywords: Biomechanics; car accidents; injury severity; road safety; Iraq